Innovative Approaches Towards Agricultural Risk Management - Kramer, Berber; Laiboni, Gabriel Munene (International Food Policy Research Institute, 2023)
Kenya’s agricultural sector is very important to its economy. However, as in other African countries south of the Sahara, it is increasingly vulnerable to vagaries of climate change, with climate-related risks affecting food production, food and income security, and having spillover effects to the wider economy. In the absence of urgent action against climate change, the economic prognosis, and impacts in terms of food security look bleak. Management of agricultural risks requires a holistic approach. To address challenges related to climate change, such as erratic weather patterns, farmers will need to adapt how they grow their crops and manage their livelihoods. This includes adopting seeds of stress tolerant varieties and using crop insurance to reduce the amount of risk that their farming enterprise faces.